CHATGPT AS A LEARNING COMPANION: NURSING STUDENTS' PERCEPTIONS OF GENERATIVE AI IN ENGLISH FOR NURSING PURPOSES USING PHENOMENOLOGICAL APPROACH - Grace Fresania Kaparang; Stephanie Tauran; Shapely Ambalao (Smart Education, 2026)
Abstract: This study explored nursing students’ perceptions of using ChatGPT in learning English for Nursing Purposes at Universitas Klabat. As English proficiency is essential for understanding medical terminology, academic nursing literature, clinical documentation, and patient communication, nursing students need language support that is relevant to their professional field. This study employed a qualitative research design using a phenomenological approach to understand students’ lived experiences with ChatGPT as an AI-assisted learning tool. Data were collected through semi-structured interviews with nursing students who had experience using ChatGPT for English learning activities. The data were analyzed using thematic analysis following Braun and Clarke’s six-step framework. The findings revealed four major themes from 8 informants interview. First, students experienced ChatGPT as an accessible learning companion that supported their understanding of nursing vocabulary, medical terminology, English articles, grammar, academic writing, and patient communication. Second, ChatGPT provided efficiency and empowerment by helping students access information quickly, complete academic tasks more easily, and increase their confidence in using English. Third, students recognized limitations and risks, including inaccurate responses, inappropriate translations, fabricated references, technical constraints, and possible dependence on AI. Fourth, students developed a more critical and responsible approach by verifying AI-generated information, using trusted references, improving prompt quality, and avoiding direct copy-paste practices. Overall, the study concludes that ChatGPT can be a useful supplementary tool for learning English in nursing education when used critically, ethically, and in combination with reliable academic sources. Keywords: ChatGPT, English for Nursing Purposes, nursing students, artificial intelligence, phenomenology, English language learning Abstrak: Penelitian ini bertujuan untuk mengeksplorasi persepsi mahasiswa keperawatan terhadap penggunaan ChatGPT dalam pembelajaran English for Nursing Purposes di Universitas Klabat. Kemampuan berbahasa Inggris sangat penting bagi mahasiswa keperawatan karena berkaitan dengan pemahaman istilah medis, literatur akademik keperawatan, dokumentasi klinis, serta komunikasi dengan pasien. Penelitian ini menggunakan desain kualitatif dengan pendekatan fenomenologi untuk memahami pengalaman hidup mahasiswa dalam menggunakan ChatGPT sebagai alat bantu pembelajaran berbasis kecerdasan buatan. Data dikumpulkan melalui wawancara semi-terstruktur dengan mahasiswa keperawatan yang memiliki pengalaman menggunakan ChatGPT dalam kegiatan pembelajaran bahasa Inggris. Data dianalisis menggunakan analisis tematik berdasarkan enam tahapan Braun dan Clarke. Hasil penelitian menunjukkan empat tema utama. Pertama, mahasiswa memandang ChatGPT sebagai pendamping belajar yang mudah diakses, terutama dalam memahami kosakata keperawatan, istilah medis, artikel berbahasa Inggris, tata bahasa, penulisan akademik, dan persiapan komunikasi dengan pasien. Kedua, ChatGPT memberikan efisiensi dan pemberdayaan karena membantu mahasiswa memperoleh informasi dengan cepat, menyelesaikan tugas akademik dengan lebih mudah, dan meningkatkan kepercayaan diri dalam menggunakan bahasa Inggris. Ketiga, mahasiswa menyadari adanya keterbatasan dan risiko, seperti jawaban yang kurang akurat, terjemahan yang tidak sesuai, referensi yang tidak dapat ditemukan, kendala teknis, serta kemungkinan ketergantungan pada AI. Keempat, mahasiswa mengembangkan penggunaan ChatGPT yang lebih kritis dan bertanggung jawab melalui verifikasi informasi, penggunaan sumber terpercaya, penyusunan prompt yang lebih jelas, dan menghindari praktik menyalin jawaban secara langsung. Penelitian ini menyimpulkan bahwa ChatGPT dapat menjadi alat bantu tambahan yang bermanfaat dalam pembelajaran bahasa Inggris keperawatan apabila digunakan secara kritis, etis, dan dikombinasikan dengan sumber akademik yang terpercaya. Kata kunci: ChatGPT, English for Nursing Purposes, mahasiswa keperawatan, kecerdasan buatan, fenomenologi, pembelajaran bahasa Inggris